2019
DOI: 10.35585/inspir.v9i2.2530
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Sistem Informasi Layanan Print Online

Abstract: 3ABSTRAK Mahasiswa seringkali mendapatkan tugas-tugas yang harus dicetak seperti makalah, laporan, skripsi, dan sebagainya sehingga kegiatan cetak dokumen menjadi sangat sering dilakukan. Kegiatan cetak dokumen di luar terasa sangat mengganggu produktivitas para mahasiswa karena dengan begitu mereka harus berjalan menuju tempat print, mengantre, dan sibuk mencari tempat print yang buka. Cuaca yang sering tidak mendukung serta harga cetak yang tidak sesuai juga menjadi salah satu faktor kurangnya kepuasan pelan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…In this research, the author suggested creating a mobile-based module for searching and ordering goods or photocopy shop services. The application system designed aims to digitize the ordering system and also search for photocopy shop locations, so that consumers can easily re-order the items they need when they run out without having to queue and wait for services to order and pay [9]. The system development method used in this research is the mobile-based waterfall model.…”
Section: Resultsmentioning
confidence: 99%
“…In this research, the author suggested creating a mobile-based module for searching and ordering goods or photocopy shop services. The application system designed aims to digitize the ordering system and also search for photocopy shop locations, so that consumers can easily re-order the items they need when they run out without having to queue and wait for services to order and pay [9]. The system development method used in this research is the mobile-based waterfall model.…”
Section: Resultsmentioning
confidence: 99%
“…Berbeda dengan mahasiswa, umumnya pekerja melakukan kegiatan mencetak dan fotokopi di dalam kantor perusahaannya secara mandiri, sebab banyak perusahaan yang telah menyediakan fasilitas mesin pencetak dan fotokopi yang dapat digunakan oleh para pekerja (Wanudjaya, 2017). Oleh sebab itu, dibanding pekerja, mahasiswa lebih sering dalam menggunakan jasa gerai percetakan dalam menunjang kegiatan mencetak dan fotokopi pada media kertas (Fadhilah et al, 2019).…”
Section: Pendahuluanunclassified